7(w-6)=-2w+48

Simple and best practice solution for 7(w-6)=-2w+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(w-6)=-2w+48 equation:



7(w-6)=-2w+48
We move all terms to the left:
7(w-6)-(-2w+48)=0
We multiply parentheses
7w-(-2w+48)-42=0
We get rid of parentheses
7w+2w-48-42=0
We add all the numbers together, and all the variables
9w-90=0
We move all terms containing w to the left, all other terms to the right
9w=90
w=90/9
w=10

See similar equations:

| 1/3x+1/2=1/5 | | 3(x-1)+7=4x+3-3(2-x) | | 151=8(6n-1)+5N | | x+3x=8x-4 | | 3(3x+4)=6(x+2) | | 9/10x=9.01/2 | | 14+-6y-3y=-4 | | 7a-4(-4a+2)=84 | | X^3+5x+16=0 | | 9/10x=91/2 | | -5|6x+36|=-360 | | X^3-5x+16=0 | | x=9=19 | | 2t-1/2=5t+1/3 | | 3n=18.75n= | | 16x^+96x+144=0 | | 6b+2(7+7b)=-106 | | 2(x-6)=3(x-+2) | | 3y+(3+-1y)=5 | | 48x+46-18x= | | .67x^2+35=87 | | 81=-3(-4a-7) | | y7=13 | | -4(3x+5)=5x-7 | | 3m-20=m+40 | | 2(-2x+6)=7x+1 | | x2+6x+9=1 | | 64=6w+16+8w | | -0,8x^2+9x+1=15 | | 8.6=1.8y-5.4 | | 0=21x2-14x+7 | | 10+1/2x=1 |

Equations solver categories